Exploiting Nanobodies in the Detection and Quantification of Human Growth Hormone via Phage-Sandwich Enzyme-Linked Immunosorbent Assay - Murad, Hossam; Assaad, Jana Mir; Al-Shemali, Rasha; Abbady, Abdul Qader (Frontiers in Endocrinology, 2017)
Background: Monitoring blood-levels of human growth hormone (hGH) in most children with short stature deficiencies is crucial for taking a decision of treatment with extended course of daily and expensive doses of recombinant hGH (rhGH or Somatropin®). Besides, misusing of rhGH by sportsmen is banned by the world anti-doping agency (WADA) and thus sensitive GH-detecting methods are highly welcome in this field. Nanobodies are the tiniest antigen-binding entity derived from camel heavy chain antibodies (HCAbs). They were successfully generated against numerous antigens including hormones. Methods: A fully nanobody-based sandwich-ELISA method was developed in this work for direct measurement of GH in biological samples. Results: Two major characteristics of nanobody were exploited for this goal; the robust and stable structure of the nanobody (NbGH04) used to capture hGH from tested samples, and the great ability of tailoring, enabling the display of the anti-GH detector nanobody (NbGH07) on the tip of M13-phage. Such huge, stable and easy-to-prepare phage-Nb was used in ELISA to provide an amplified signal. Previously, NbGH04 was retrieved on immobilized hGH by phage display from a wide “immune” cDNA library prepared from a hGH-immunized camel. Here, and in order to assure epitope heterogeneity, NbGH07 was isolated from the same library using NbGH04-captured hGH as bait. Interaction of both nanobodies with hGH was characterized and compared with different anti-GH nanobodies and antibodies. The sensitivity (~ 0.5 ng/ml) and stability of the nanobody-base sandwich ELISA were assessed using rhGH before testing in the quantification of hGH in blood sera and cell culture supernatants. Conclusions: In regard to all advantages of nanobodies; stability, solubility, production affordability in E. coli and gene tailoring, nanobody-based phage sandwich ELISA developed here would provide a valuable method for hGH detection and quantification.